Interplay between Risk Factors and Coronary Artery Calcium in Middle-Aged and Elderly Symptomatic Patients - Lu Zeng; Jun-Yi Luo; Fen Liu; Zhuo-Ran Zhang; Ya-Jing Qiu; Fan Luo; Xin-Xin Tian; Xiao-Mei Li; Yi-Ning Yang (Reviews in Cardiovascular Medicine, 2023)
Background: The prognostic value of coronary artery calcium (CAC) combined with risk factor burdens in middle-aged and elderly patients with symptoms is unclear. Methods: A cohort study comprising 7432 middle-aged and elderly symptomatic patients (aged above 55 years) was conducted between December 2013 and September 2020. All patients had undergone coronary computed tomography angiography, and the Agatston score were used to measure CAC scores. The primary outcome was major adverse cardiac and cerebrovascular events (MACCE), which was defined as a composite outcome of nonfatal myocardial infarction, revascularization (percutaneous coronary intervention or coronary artery bypass graft), stroke, and cardiovascular death. Congestive heart failure, cardiogenic shock, malignant arrhythmia, and all-cause mortality were defined as the secondary outcomes. Results: There are 970 (13%) patients with CAC 0–10, 2331 (31%) patients with CAC 11–100, and 4131 (56%) patients with CAC ≥101. The proportion of patients aged 55–65 years, 65–75 years and ≥75 years was 40.7%, 38.1% and 21.2%, respectively. The total number of MACCEs over the 3.4 years follow-up period was 478. The percentage of CAC ≥101 was higher among the 75-year-old group than the 55–65-year-old group, increasing from 46.5% to 68.2%. With the increase in the CAC score, the proportion of patients aged ≥75 years increased from 12.9% to 25.8%, compared to those aged 55–65 years. The number of risk factors gradually increased as the CAC scores increased in the symptomatic patients aged over 55 years and the similar tendencies were observed among the different age subgroups. The proportion of non-obstructive coronary artery disease (CAD) was comparable between the three age groups (53.5% vs 51.9% vs 49.1%), but obstruction CAD increased with age. The incidence of MACCE in the group with CAC ≥101 and ≥4 risk factors was 1.71 times higher (95% confidence interval (CI) 1.01–2.92; p = 0.044) than the rate in the group with CAC ≥101 and 1 risk factor. In the CAC 0–10 group, the incidence of MACCE in patients aged ≥75 years was 12.65 times higher (95% CI: 6.74–23.75; p < 0.0001) than that in patients aged 55–65 years. By taking into account the combination of CAC score, age, and risk factor burden, the predictive power of MACCE can be increased (area under the curve (AUC) = 0.614). Conclusions: In symptomatic patients aged 55 or above, a rise in age, CAC scores, and risk factor burden was linked to a considerable risk of future MACCE. In addition, combining CAC scores, age and risk factors can more accurately predict outcomes for middle-aged and elderly patients with symptoms.